Marital satisfaction of the spouses coming from from broken and incomplete families - Wańczyk-Welc Anna; Marmola, Małgorzata (Zakład Historii Edukacji Instytutu Pedagogiki Uniwersytetu Wrocławskiego, 2017)
The article presents the research concerning marital satisfaction of the spouses coming from from broken and incomplete families. Marital satisfaction depends on many factors; one of these can be family predispositions, especially “experience gained from the family of origin”. In this context, the process of intergenerational transmission reinforces the family or weakens it and using the resource of the family of origin can be a threat to younger generations. The foregoing assumption became a central subject of discussion and it is a starting point to this research. Marital satisfaction was ascertained using the Questionnaire of the Attuned Marriage developed by M. Plopa and J. Rostowski. The questionnaire describes the quality of the marriage as perceived by each spouse. A general measurement of the bounds and the measurement of the factors such as closeness, self-realization, similarity and disappointment can be achieved.
Keywords: martial satisfaction; family of origin; broken family; incomplete family